Badminton investigations applied to sports sciences: A bibliometric and scientometric study from 1991 to 2024 - Algislayne Fechtner Coenga; Schelyne Ribas; Geovanna Shannayra De Souza Silva; David Cabello Manrique; Tatiane Mazzardo; Layla Maria Campos Aburachid (Journal of Physical Education (Maringá), 2025)
The study identified the scientific production of articles about Badminton around Sports Sciences between 1991 and 2024 considering the subfields of Sports Sciences, the year, continent and journals of publication, and the characteristics of the sample of studies in terms of size, level of performance, gender and age group. The method used to collect the data was Bibliometrics and Scientometrics, using the term “badminton”. The SCOPUS database was used to search for articles in English, Spanish and Portuguese languages. With a resulting sample of 477 articles, the sub-areas with the highest production were Sports Training (25.79%), followed by Health (18.66%). In 2023 there was the highest production about badminton (63), Europe was the continent with the highest number of published articles (235) and the Journal of Sports Science was the journal with the highest number of articles (19). It was concluded that the production of articles on Badminton is a field on the rise, since 2012 there has been a diversification of publications in the subfields of Sports Sciences and the subjects of the studies range from the level of sports initiation to high performance.